2012
DOI: 10.1021/es2035152
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Environmental Exposure of Honeybees to Particulate Matter Containing Neonicotinoid Insecticides Coming from Corn Coated Seeds

Abstract: Since seed coating with neonicotinoid insecticides was introduced in the late 1990s, European beekeepers have reported severe colony losses in the period of corn sowing (spring). As a consequence, seed-coating neonicotinoid insecticides that are used worldwide on corn crops have been blamed for honeybee decline. In view of the currently increasing crop production, and also of corn as a renewable energy source, the correct use of these insecticides within sustainable agriculture is a cause of concern. In this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
144
0
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 175 publications
(154 citation statements)
references
References 28 publications
4
144
0
6
Order By: Relevance
“…It has been shown that bees can be contaminated with potentially lethal doses of insecticide simply by flying in the vicinity of a pneumatic drilling machine using seeds coated with insecticide (Marzaro et al, 2011;Girolami et al, 2012). The fragments of this coating are emitted into the atmosphere and constitute a toxic cloud the size of which may be estimated at some tens of metres in diameter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that bees can be contaminated with potentially lethal doses of insecticide simply by flying in the vicinity of a pneumatic drilling machine using seeds coated with insecticide (Marzaro et al, 2011;Girolami et al, 2012). The fragments of this coating are emitted into the atmosphere and constitute a toxic cloud the size of which may be estimated at some tens of metres in diameter.…”
Section: Introductionmentioning
confidence: 99%
“…Observations are done at the level of the colony and only individual observations on bees are included insofar as they may affect colony development. In principle, guttation water would not be a major source of exposure given that normally these droplets occur mainly in early plant developmental stages (Girolami et al, 2009;Tapparo et al, 2012). However, the individual geographical and meteorological conditions of each area should be considered to exclude this potential exposure route.…”
Section: Introductionmentioning
confidence: 99%
“…Using this theoretical air concentration an exposure level for bees flying to and from their foraging areas can be calculated by multiplying the air exposure volume by the insecticide air concentration, resulting in a dose of 9.2 ng/bee, a deposition rate of 6.25 ng/bee per 1μg ai/ m 3 . The far higher levels reported when bees were held in cages (Tapparo et al, 2012) reflects an artificial situation in which bees could not move through or away from the dust plume. This is demonstrated by the lower residues in live bees sampled at the hives following application of clothiandin treated seed in which residues of 1.8 ng/bee were detected (Chauzat, Martel et al 2010) which suggests that the use of the concentration in air over the treated field may be protective but not unrealistic.…”
Section: Spray Drift and Dustmentioning
confidence: 96%
“…Pneumatic planters are widely used and have been identified as a source of dispersion of abraded particles during maize drilling since 2003 (Greatti et al 2003). Many other field experiments identified sowing with pneumatic drilling machines as an important source of environmental contamination (Krupke et al 2012;Pochi et al 2012;Tapparo et al 2012). The release into the atmosphere of particulate matter containing insecticides causes the contamination of vegetation surrounding the field, with the consequent exposure of nontarget animals to sublethal dose of insecticides (Greatti et al 2006;Stewart et al 2014).…”
Section: Air and Dustmentioning
confidence: 99%